PENGARUH GAYA KEPEMIMPINAN STORE MANAGER TERHADAP KINERJA KARYAWAN PT. SUSHI TEI INDONESIA KHUSUSNYA OUTLET GANDARI CITY JAKARTA - Indri Astuti (Sekolah Tinggi Manajemen IMMI, 2018)
One of the tools used to generate employee performance against a company is the leadership style of the company itself. Basically, employees should be treated properly, justly and healthily in caring, giving the duties and responsibilities of a leader, so they can feel comfortable in an organization or company itself. This study aims to determine how much influence the leadership style of managers on employee performance in PT. Sushi Tei Indonesia especially at outlet Gandaria City Jakarta. Research method in this research is method of purposive sampling method. The results showed that leadership style in PT. Sushi Tei Indonesia especially at Gandaria City Jakarta outlet is charismatic and assertive, and employee performance is included in good / high category. The result of statistical analysis shows that there is influence of store manager's leadership style to employee performance in PT. Sushi Tei Indonesia especially at Gandaria City Jakarta outlet is 23.8% while the rest of 76.2% (100% - 23.8%) is explained by other variables outside the regression model in this study. Suggestions that can be conveyed by the writer is considered Store Manager need to pay more attention to the performance of each employee, because there are still employees who throw an error to other co-workers, if things are not immediately followed up feared may affect employee performance going forward. Keyword : Leadership, performance,